(untitled) (Communications in Mathematical Research, 2021)
In this paper, we study the existence of the reflexive, reflexive self-adjoint and reflexive positive solutions to some operator equations with respect to the generalized reflection operator dual (P,Q). We derive necessary and sufficient conditions for the solvability of these equations and provide a detailed description of the solutions in the solvable case by using the Moore-Penrose inverses.